Three-dimensional transient numerical simulation for gas exchange process in a four-stroke motorcycle engine - 王春发 陈国华 罗马吉 杨万里 (Journal of Zhejiang University. A. Science, 2005)
Three-dimensional transient numerical simulation of gas exchange process in a four-stroke motorcycle engine with a semi-spherical combustion chamber with two tilt valves was studied. Combination of the grid re-meshing method and the snapper technique made the valves move smoothly. The flow structure and pattern in a complete engine cycle were described in detail. Tumble ratios around the x-axis and y-axis were analyzed. Comparison of computed pressure with experimental pressure under motored condition revealed that the simulation had high calculation precision; CFD simulation can be regarded as an important tool for resolving the complex aerodynamic behavior in motorcycle engines.